Heteromeric TRPV4/TRPC1 channels mediate calcium-sensing receptor-induced relaxations and nitric oxide production in mesenteric arteries: comparative study using wild-type and TRPC1-/- mice - Greenberg, Harry Z. E. (2019)
Fil: Greenberg, Harry Z. E. University of London. Vascular Biology Research Centre, Molecular & Clinical Sciences Research Institute; Inglaterra